2017
DOI: 10.1370/afm.2044
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Training Institution Practice Costs, Quality, and Other Characteristics on Future Practice

Abstract: PURPOSE Medicare beneficiary spending patterns reflect those of the 306 Hospital Referral Regions where physicians train, but whether this holds true for smaller areas or for quality is uncertain. This study assesses whether cost and quality imprinting can be detected within the 3,436 Hospital Service Areas (HSAs), 82.4 percent of which have only 1 teaching hospital, and whether sponsoring institution characteristics are associated. METHODSWe conducted a secondary, multi-level, multivariable analysis of 2011 M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…Health and health care disparities are inequities among vulnerable populations linked to inadequate care and poor health outcomes. 3 The definitions below are provided as context for these concepts.…”
Section: Box: Health Equity Health Disparities and Health Care Dispmentioning
confidence: 99%
“…Health and health care disparities are inequities among vulnerable populations linked to inadequate care and poor health outcomes. 3 The definitions below are provided as context for these concepts.…”
Section: Box: Health Equity Health Disparities and Health Care Dispmentioning
confidence: 99%
“…In a study of the long-term "imprint" of training, Phillips and colleagues find that the spending pattern of physicians training in high cost vs low cost Hospital Service Areas persists long after training. 13 An article by authors from the Patient-Centered Outcomes Research Institute (PCORI) shares an Engagement Rubric developed from multiple sources. Building on decades of prior work in participatory research by others, the PCORI Engagement Rubric provides a framework for involving patients and other stakeholders in all phases of research.…”
Section: Conflict Of Interest: Kurt Stange Has Been a Member Of The Nmentioning
confidence: 99%
“…6 Medical education thus has a responsibility to not only equip students with a nuanced understanding of value, but also support the development of high-value practice patterns aligned with this aim. 7 Prior studies have demonstrated relationships between physicians' experiences during residency and their subsequent knowledge, 8 attitudes, 9 behaviors, 10,11 and patient outcomes 12 related to high-value care. These relationships are evident as early as internship 13 and persist for up to 15 years after training.…”
Section: Introductionmentioning
confidence: 99%
“…These relationships are evident as early as internship 13 and persist for up to 15 years after training. 10,11 This suggests residency training contributes to an imprinting process whereby learners develop practice patterns resembling those they observe in the learning environment. 11,12 Studies like these highlight the importance of the graduate medical education training environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation